Cell division site placement and asymmetric growth in mycobacteria. - Graham Joyce; Kerstin J Williams; Matthew Robb; Elke Noens; Barbara Tizzano; Vahid Shahrezaei; Brian D Robertson (PLoS ONE)
Mycobacteria are members of the actinomycetes that grow by tip extension and lack apparent homologues of the known cell division regulators found in other rod-shaped bacteria. Previous work using static microscopy on dividing mycobacteria led to the hypothesis that these cells can grow and divide asymmetrically, and at a wide range of sizes, in contrast to the cell growth and division patterns observed in the model rod-shaped organisms. In this study, we test this hypothesis using live-cell time-lapse imaging of dividing Mycobacterium smegmatis labelled with fluorescent PBP1a, to probe peptidoglycan synthesis and label the cell septum. We demonstrate that the new septum is placed accurately at mid-cell, and that the asymmetric division observed is a result of differential growth from the cell tips, with a more than 2-fold difference in growth rate between fast and slow growing poles. We also show that the division site is not selected at a characteristic cell length, suggesting this is not an important cue during the mycobacterial cell cycle.